An examination of the literature relating to issues affecting the human variable in just-in-time environments - Power, Damien J. (Technovation)
There has been an extensive body of research conducted into the technical aspects of the just-in-time (JIT) manufacturing methodology, particularly prior to 1990. It is only in more recent times that the focus has turned toward the more subtle people-related aspects. The recognition of JIT as a truly holistic approach to managing manufacturing operations has led to an appreciation of the importance of the role played by the human variable as well as an emphasis on the impact that organisational structure and management style can have on successful operation. This article examines and analyses the content of a wide range of articles related to issues such as : the need for change in corporate culture, the role of organisational structures, factors significantly impacting chances of success, the importance of employee involvement, how best to involve employees, the importance of training, how/whom/when to train, different team-based organisational structures, the impact of changing roles on various levels of the organisation, and the appropriateness of particular change management strategies. An overall picture of the current state of thinking on these issues is thus developed and the importance of these factors to the successful implementation and operation of JIT highlighted. Opportunities for further research in this important area are identified.